2010
DOI: 10.1108/14635781011048867
|View full text |Cite
|
Sign up to set email alerts
|

REIT excess dividend and information asymmetry: evidence with taxable income

Abstract: Purpose -US real estate investment trusts (REITs) typically distribute more dividends than required by tax regulations. This paper aims to focus on discretionary dividends, and examines the impact of information asymmetry on this excess component of dividends. Design/methodology/approach -This paper considers a set of US REITs with reported taxable income figures over the 2000-2007 period, and employs regression analysis to examine the influence of information asymmetry on the excess component of dividends. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…As a conclusion, despite the unique structure of REITs where a mandatory dividend pay-out 90% of total taxable income is imposed and it is believed to be able to mitigate the agency problem in REITs, this study show the earnings management problem still exists in REITs, indicating that there is a need for specific governance mechanisms that can mitigate this problem in Asian REITs. (Ben-Shahar, Sulganik, & Tsang, 2010;Edelstein et al, 2009;Ghosh & Sirmans, 2006;Ghosh & Sun, 2013;Hayunga & Stephens, 2009;Lee, Chiu, Lee, Chiang, & Jr, 2010;Mooradian & Yang, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…As a conclusion, despite the unique structure of REITs where a mandatory dividend pay-out 90% of total taxable income is imposed and it is believed to be able to mitigate the agency problem in REITs, this study show the earnings management problem still exists in REITs, indicating that there is a need for specific governance mechanisms that can mitigate this problem in Asian REITs. (Ben-Shahar, Sulganik, & Tsang, 2010;Edelstein et al, 2009;Ghosh & Sirmans, 2006;Ghosh & Sun, 2013;Hayunga & Stephens, 2009;Lee, Chiu, Lee, Chiang, & Jr, 2010;Mooradian & Yang, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Downs, Guner, and Patteson (2000) and McDonald, Nixon, and Slawson (2000) examined the unfavourable collection cost component of bid‐ask spreads and find significant impacts of REIT dividend policies on their asymmetric information measures. Hardin and Hill (2008) and Lee, Chiu, Lee, Chiang, and Slawson (2010) also found that excess dividends can be used to help REITs become more transparent, and thus have better access to the capital market. Capozza and Seguin (1998) covered the time period from 1985 to 1992.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, a higher dividend yield seems to bring more benefits to REIT investors so that the required REIT returns may decrease with dividend yield. Besides, Lee et al (2010) document that REITs with higher degree of asymmetric information pay out more dividends. So, the required REIT returns may be associated with dividend yield from the information asymmetry perspective.…”
Section: Other Control Variablesmentioning
confidence: 99%